Construction in the Muslim world - a factual analysis and policy implications - Abdul Rashid, Khairuddin; Mohit, Mohammad Abdul (2009)
Widespread poverty, inadequacies in food, shelter and meaningful employment due to the lack of economic development, the lack of easy access to schools and education, the lack of freedom and political representation, etc in some of the least developed developing countries of the Muslim world are common knowledge. Attempts at developing and implementing appropriate strategies have been made and are continuing in effort to bring about economic development to these countries but the situation remained. In this paper the authors argued that one effort to bring about economic development is through the construction sector where construction delivers the much needed basic infrastructures. The latter would then enable economic activities to be carried out and therefore promote socio-economic growth and development. An examination on the size and contribution of the construction sectors of the countries of the Muslim world to their respective economies was carried out and the outcome formed a basis in considering policy implications on how construction could be used as a catalyst to bring about sustainable economic growth and development to these countries. The key results from the examination are: majority of the construction sectors of the countries of the Muslim world make small contribution to their GDP; at per capita level, most of the countries of the Muslim worlds' construction GDPs are very small; and per capita construction GDP is positively correlated to per capita GDP and GDP from the industrial sector but is negatively related to other sectoral GDPs. In terms of policy implications, topping the list include development of the countries of the Muslim world, in terms of enhancing per capita income or GDP, relies with the generation of construction and industrial sector GDPs and not with other sectoral GDPs and the countries of the Muslim world should promote active and mutual cooperation. In the paper the Muslim world refers to the member countries of the Organization of the Islamic Conference or OIC.